Hormonal replacement therapy in hormone-dependent cancers - Asendrych, Alicja; Deptała, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2004)
An increased cancer incidence rate at menopausal and andropausal age as well as the effects of oncological therapy lead some people to suffering from a deficiency of sex hormones. The management of healthy people usually involves the use of hormone replacement therapy (HRT). However, an approach for persons who were treated because of hormone-dependent tumors, or for healthy individuals who have an increased risk of developing cancer has to be determined. Estrogen impact on the risk of breast cancer is well documented. New data have confirmed previous observations that progesterone and testosterone are involved in the pathogenesis of breast cancer and prostate cancer, respectively. The classic oncologists’ opinion has presumed that HRT was contraindicated in such cases. Is the opinion still valid in the light of advancement of contemporary scientific reports? Some data continue to show more harm than good for long-term users of HRT. Thus, a considerable selection of candidates for HRT and precise definition of duration are required. This paper provides a comprehensive review of the use of HRT in oncology either to improve the quality of life or to prevent several diseases. When summarizing the data, it is necessary to point out that persons with a history of breast cancer, uterus cancer and prostate cancer should be given as a first-line therapy an alternative approach, instead of HRT. However, those uterus cancer cases failing the alternative approach, can get HRT. In patients with a history of ovarian cancer, there is no contraindications for HRT whatsoever.